Intraoperative Nomograms, Based on One-Step Nucleic Acid Amplification, for Prediction of Non-sentinel Node Metastasis and Four or More Axillary Node Metastases in Breast Cancer Patients with Sentinel Node Metastasis - Shimazu, Kenzo (Ann Surg Oncol, 2018)
BACKGROUND: One-step nucleic acid amplification (OSNA) for cytokeratin 19 messenger RNA is an intraoperative diagnostic procedure for the detection of lymph node metastasis. OBJECTIVE: This study aimed to construct intraoperative nomograms using OSNA for the prediction of non-sentinel lymph node (NSLN) metastasis and four or more axillary lymph node (ALN) metastases. METHODS: Of the 4736 breast cancer patients (T1-3, N0) who underwent sentinel lymph node (SLN) biopsy and had SLNs examined intraoperatively with OSNA, 623 with SLN metastasis treated with completion ALN dissection (cALND) were retrospectively analyzed, and were randomly divided into training (n = 312) and validation (n = 311) sets. RESULTS: Of the clinicopathological parameters available preoperatively and intraoperatively, the multivariate analysis of the training set revealed that clinical tumor size and total tumor load (TTL) determined by OSNA were significantly associated with NSLN metastasis, and that clinical tumor size, number of macrometastatic SLNs, and TTL were significantly associated with four or more ALN metastases. Nomograms for NSLN metastasis and four or more ALN metastases were constructed using these parameters, and their area under the receiver operating characteristic curve (AUC) of the validation set were both 0.70, with a diagnostic accuracy similar to that of previously reported postoperative nomograms. CONCLUSIONS: We constructed intraoperative nomograms using OSNA for the prediction of NSLN metastasis and four or more ALN metastases. These nomograms are as accurate as the conventional postoperative nomograms and might be helpful for decision making regarding the indication for cALND or the choice of adjuvant chemotherapeutic regimens and radiation field. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1245/s10434-018-6633-0) contains supplementary material, which is available to authorized users.